2017
DOI: 10.1186/s13756-017-0177-0
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for relapse or persistence of bacteraemia caused by Enterobacter spp.: a case–control study

Abstract: Background Enterobacter spp. possess chromosomal AmpC beta-lactamases that may be expressed at high levels. Previous studies have demonstrated a risk of relapsed bacteraemia following therapy with third generation cephalosporins (3GCs). What additional factors predict microbiological failure in Enterobacter bacteraemia is unclear. We aimed to determine factors associated with microbiological failure in Enterobacter bacteraemia.MethodsWe retrospectively identified cases of bacteraemia caused by Enterobacter spp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 30 publications
(31 reference statements)
1
18
2
Order By: Relevance
“…In this retrospective analysis of bacteraemia from a single hospital in Kathmandu, we report a 13.5% bacterial isolation rate from blood cultures, which is comparable with other bacteraemia studies from Nepal and elsewhere ( 5 , 20 22 ). Similarly, the array of isolated organisms was similar to those reported in other studies investigating the etiology of bloodstream infections ( 2 , 3 , 22 25 ), and childhood septicaemia ( 5 , 11 , 25 , 26 ). The most common Gram-negative, non- Salmonella organisms to be isolated from blood cultures within this population were Enterobacter spp., followed by Acinetobacter spp., E. coli and Klebsiella spp., a distribution that has been observed previously ( 3 , 5 , 23 , 27 ).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In this retrospective analysis of bacteraemia from a single hospital in Kathmandu, we report a 13.5% bacterial isolation rate from blood cultures, which is comparable with other bacteraemia studies from Nepal and elsewhere ( 5 , 20 22 ). Similarly, the array of isolated organisms was similar to those reported in other studies investigating the etiology of bloodstream infections ( 2 , 3 , 22 25 ), and childhood septicaemia ( 5 , 11 , 25 , 26 ). The most common Gram-negative, non- Salmonella organisms to be isolated from blood cultures within this population were Enterobacter spp., followed by Acinetobacter spp., E. coli and Klebsiella spp., a distribution that has been observed previously ( 3 , 5 , 23 , 27 ).…”
Section: Discussionsupporting
confidence: 83%
“…bacteraemia ( 28 ). This escalation is cause for concern, as this bacterial genus presents particular challenges for the selection of optimal antimicrobial therapy due to the presence of chromosomally encoded AmpC beta-lactamases ( 25 ). Among the Gram-positive organisms (excluding Coagulase negative Staphylococci , which were reported for neonates only), S. aureus , Non-haemolytic Streptococci and S. pneumoniae were the most commonly isolated pathogens from blood cultures; this is also a common array of organisms associated with bacteraemia ( 5 , 8 , 24 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…A complete review of the articles yielded 5 new studies [9–13], which were used to update the previous meta-analysis of 8 studies [5] comprising 665 patients. One study included patients who were already reported in the previous meta-analysis [11] and so to avoid double counting we only included those patients in the later group. In total, 13 studies (including our unpublished data) and 1021 patients were included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…This bacteremia database involves 159 case-controlled cases of bacteraemia occurring among those of age 17 or over at four hospitals in Queensland and New South Wales, Australia between 1998 and 2015 ( Harris et al 2017 ). The data is used to predict risk factors associated with relapsed infection in patients with Enterobacer bacteraemia, based on multiple factors including age, sex, location, source of infection, hospital location, co-morbid conditions, and many other clinical factors.…”
Section: [A44] Bacteraemiamentioning
confidence: 99%